Aquaculture and marine protected areas: Potential opportunities and synergies. (September 2017) - Le Gouvello, Raphaëla; Hochart, Laure‐Elise; Laffoley, Dan; Simard, François; Andrade, Carlos; Angel, Dror; Callier, Myriam; De Monbrison, David; Fezzardi, Davide; Haroun, Ricardo; Harris, Alasdair; Hughes, Adam; et al.
Abstract: To meet the Convention on Biological Diversity's Aichi Target 11 on marine biodiversity protection and Aichi Target 6 on sustainable fisheries by 2020, as well as the Sustainable Development Goal (SDG) 2 on food security and SDG 14 on oceans by 2030, there is an urgent need to rethink how best to reconcile nature conservation and sustainable development. This paper argues for effective governance to support processes that apply principles of sustainable development and an ecosystem approach to decide about economic activities at sea such as aquaculture. It describes opportunities, benefits and synergies between aquaculture and MPAs as a basis for wider debate. The scope is not a comprehensive analysis of aquaculture and MPAs, but rather to present examples of positive interactions between aquaculture activities and MPAs. The unintended negative consequences are also discussed to present balanced arguments. This work draws from four workshops held in 2015 and 2016 and used to collect information from about 100 experts representing various sectors and perspectives. It is recognized that aquaculture is an important activity in terms of sustainable development. It can play a role in providing food security, poverty alleviation and economic resilience, in particular for MPA local communities, and contribute to wild stock enhancement, as an alternative to overfishing and for providing services to the ecosystem. This study showed that there is a need from both aquaculture and MPA sides for clarity of objectives and willingness for open and extensive dialogue. The paper concludes by describing a number of tools and methods for supporting greater synergies between aquaculture and MPAs. The results from this work have already helped to build a common understanding between conservation and aquaculture and initiate a rapprochement for increasing synergies.